2019
DOI: 10.1103/physrevc.100.064905
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initial-state momentum anisotropy on the final-state collectivity in small collision systems

et al.

Abstract: A multi-phase transport model is used to understand the origin of long-range collective azimuthal correlations in small-system collisions. To disentangle between collectivity associated with initialstate intrinsic momentum anisotropy and the collectivity arising as a final-state response to the collision geometry, we studied the development of collectivity in 5.02 TeV p+Pb collisions with both initial-state and final-state effects included. We find that the initial momentum anisotropy may not be fully isotropi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…But for small systems such explanation is a matter of active debate, see e.g. the recent works [20,21,22], and initial state dynamics have also been invoked.…”
Section: Introductionmentioning
confidence: 99%
“…But for small systems such explanation is a matter of active debate, see e.g. the recent works [20,21,22], and initial state dynamics have also been invoked.…”
Section: Introductionmentioning
confidence: 99%
“…However, the case 2 corresponds to the case where the test particles have an initial collective flow due to their common initial velocities. Note that the initial collective flow is only introduced to the test particles for case 2, which is different from our previous study where the initial collectivity was introduced to all particles of the system [35]. If we consider that the mass of the test particle is 0.05 GeV (since we always take the test particles as light quarks), with the initial velocity β the transverse momentum p T = β/( 1 − β 2 )m q ≈ 0.1 GeV/c.…”
Section: B Test Particle Methodsmentioning
confidence: 88%
“…It can be basically classified into two categories depending on whether the origin comes from the initial or final state. The initial state of color glass condensate (CGC) has also been proposed as a possible mechanism, contributing to the experimentally measured 'flow' in small colliding systems [27][28][29][30][31][32][33][34][35]. The final state of hydro- * glma@fudan.edu.cn dynamics also can transform the initial geometric asymmetry into the final momentum anisotropic flow through the pressure gradient of the QGP [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that small collision systems such as p + p and p + A in highmultiplicity present resembling properties with large A + A collisions [39]. Due to minor size and short lifetime, small-size A+A systems may undergo a modified dynamical process and are expected to shed light on initial fluctuation effects on momentum distribution in the final stage [25,26,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%